Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3389/fnagi.2022.860571
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Prognostic Characteristics of Recurrent Intracerebral Hemorrhage: A Contrast to First-Ever ICH

Abstract: This study aimed to compare clinical and prognostic characteristics between recurrent and first-ever ICH. Four thousand twelve patients entered the study, and 64% of them were male. The median age is 62 years (interquartile range, 55–71). Among them, 3,750 (93.5%) patients had no experience of previous ICH, and 262 (6.5%) patients were considered as recurrent ICH. We compared demographic data, baseline clinical characteristics, imaging information, hematological parameters, and clinical outcomes between recurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…Compared with previous studies, we found that the incidence of pulmonary disease (80.6% vs. 11.1%) and cerebrovascular disease (62.5% vs. 23.5%) was particularly high in the elderly population. In addition, pulmonary [18][19][20] and cerebrovascular [21,22] diseases have been proven to play an important role in the prognosis of ICH patients. A previous study focused on functional outcome after 1 year of ICH [12], and our study demonstrates that CCI, as a sum score weighted according to the presence of various comorbidities, also has an impact on the short-term prognosis of elderly ICH patients.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with previous studies, we found that the incidence of pulmonary disease (80.6% vs. 11.1%) and cerebrovascular disease (62.5% vs. 23.5%) was particularly high in the elderly population. In addition, pulmonary [18][19][20] and cerebrovascular [21,22] diseases have been proven to play an important role in the prognosis of ICH patients. A previous study focused on functional outcome after 1 year of ICH [12], and our study demonstrates that CCI, as a sum score weighted according to the presence of various comorbidities, also has an impact on the short-term prognosis of elderly ICH patients.…”
Section: Discussionmentioning
confidence: 99%
“…Disease severity was assessed using the National Institutes of Health Stroke Scale (NIHSS) score and the Glasgow Coma Scale (GCS) score. 26 , 27 Plasma C3 levels were quantitatively measured with a Coulter reagent according to the manufacturer's instructions on the Beckman Coulter AU5800 clinical chemistry analyzer (Beckman Coulter Inc., California, USA). The test was performed and analyzed by the same technician.…”
Section: Methodsmentioning
confidence: 99%
“…The disease severity was assessed utilizing the National Institutes of Health Stroke Scale (NIHSS) score and the Glasgow Coma Scale (GCS) score by trained neurologists at admission ( Currò et al, 2022 ; Wan et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%